PEMANFAATAN LAGU-LAGU ANAK DALAM PEMBELAJARAN TEMATIK DI TK IPAC CHANDRA KUSUMA SCHOOL MEDAN - Suheri, Eko (Universitas Negeri Medan, 2017)
The world™s children are playing anywhere and any time, children always foundtime to play. The aim of this study, 1) to know learning thematic. 2) to know themethods used. 3) to know the results of thematic learning children™s songs. 4) todetermine the constraints faced by teachers. The study describes the theoryutilization of instructional media, Theory of children™s songs, thematic theorywhich explains the thematic is a complex model by combining multiple subjects ina single theme. The method used in this research is qualitative descriptivemethods. Data collected by literature study method, observation and observations,interviews, documentation and data analysis techniques. This study took place inIPAC Chandra Kusuma School Medan. Results utilization of thematic learning inearly childood. Thematic is a complex model by combining multiple subjects in asingle theme. Thematic learning outcomes that help the child to come forward andtheir expression in terms of singing and speech. Learning methods are usedlecture and demonstration methods. Constraints faced by teaching the differencein intelligence levels between children with one another. And the lack of effectivelearning time because the only available half an hour of learning.